Innovation in the agricultural and food sector: Divergences and complementarities - Nardone G.; Pepe A.; Seneen G. de (Innovation in the Mediterranean agrifood sector. Concepts, experiences and actors in a developing ecosystem, 2016)
Innovation is a particularly complex concept, and offers a great many levels of interpretation. This chapter focuses on three different approaches to innovation: economic, technological and managerial. The dissemination of innovation in agriculture is as necessary as it is complex, but it is not always easy to convince a large number of farms to adopt new technologies. The main obstacles lie in the structural characteristics of Mediterranean agriculture, with a large number of small or very small family-run farms scattered across the territory, and farmers who are often old and poorly educated. While the main source of farm innovation remains external, the food sector tends to generate internal innovation. Today’s food industry seems increasingly less “supplier-dominated”, and more of a sector in which companies must be able to maintain a balance between technology-push and demand-pull innovations. Using the results of an analytical study at the local level, the chapter considers the differences in the propensity to innovation of two kinds of business: farming and food processing. Solutions are offered for aligning the two innovation systems and making them more efficient.